STRUCTURE AND FUNCTION OF THE CARDIOVASCULAR SYSTEM OF THE HUMAN BODY - Juraqulova Diyora; Isayeva Sevinch; Ruzieva Maftuna; Baxronov Davronbek (Web of Journals Publishing, 2024)
This article describes the structure of each of the cardiovascular system and its operation.
Keywords: Cardiac topography, Cardiac automatism, Endocardium, Myocardium, Epicardium, Regurgitation, Tricuspid valve, Mitral valve, Bundle of Hiss, Ashof-Tovar node, Kis-Flak node, Purkinje fibers.